DOI: 10.17077/etd.yq2h2khz
|View full text |Cite
|
Sign up to set email alerts
|

A biofilm-based aging model for testing degradation of dental adhesive microtensile bond strength

Abstract: The objective of this work was to develop a short-term, clinically simulative, biofilm-based aging/storage model for lab testing of newer dental adhesives in order to predict their long-term performance. To do this we tested the hypothesis that 15 days of biofilm challenge with cariogenic bacterial species, Streptococcus mutans (SM) and Streptococcus sobrinus (SS), would produce similar or a greater reduction in microtensile bond strength (μTBS) of dental adhesives as compared to a standard 6 months of water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 92 publications
(210 reference statements)
0
5
0
Order By: Relevance
“…After that, they were placed in a six wells tissue culture plate (Falcon 353046, Corning Inc.) and kept at 37 o C. This BHI medium was then added and supplemented with 0.5% sucrose to promote the establishment of a biofilm on the composite sticks within each well for 24 hours. The (BHI) growth medium was changed every day for the 15 days [39] resulting in a thick adapted biofilm layer [ Figure 4]. Three additional specimens from each composite material were fabricated and immersed in BHI for 15 days.…”
Section: Aging Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After that, they were placed in a six wells tissue culture plate (Falcon 353046, Corning Inc.) and kept at 37 o C. This BHI medium was then added and supplemented with 0.5% sucrose to promote the establishment of a biofilm on the composite sticks within each well for 24 hours. The (BHI) growth medium was changed every day for the 15 days [39] resulting in a thick adapted biofilm layer [ Figure 4]. Three additional specimens from each composite material were fabricated and immersed in BHI for 15 days.…”
Section: Aging Methodsmentioning
confidence: 99%
“…The type of solvent and storage medium affect the rate of penetration of the solvent through the material. Water storage is considered the standard and recommended type of solvent by the International Organization for Standardization (ISO 37]) for aging simulation (Indrani, Cook [38], Jain [39]). Ferracane et al (1990) found that a solution of 75% of ethanol/ 25% water significantly improved the uptake of the solvent compared to water alone and this finding was verified in another study (Ferracane and Condon [19], Ferracane [15]).…”
Section: One Of the Degradation Processes In The Oral Environment Is mentioning
confidence: 99%
See 3 more Smart Citations